2022
DOI: 10.18786/2072-0505-2022-50-015
|View full text |Cite
|
Sign up to set email alerts
|

Acute arthritis associated with COVID-19

Abstract: Coronavirus infection (COVID-19) is usually characterized by respiratory symptoms, but can have a wide range of clinical manifestations. The growing interest is focusing on the short-term and long-term immune-mediated sequelae triggered by the COVID-19. One of these complications is post-infectious arthritis, classified by some authors as reactive. This paper summarizes and analyzes 25 clinical cases of COVID-19-associated acute arthritis that have been published from January 2020 to November 2021. The mean ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…One of the key cardiovascular manifestations observed in NiV infection is myocarditis, characterized by myocardial inflammation 4 , 5 . Myocarditis can lead to myocardial dysfunction, arrhythmias, and even heart failure 5 7 . Histopathological studies have revealed lymphocytic infiltrates in the myocardium of NiV-infected individuals, indicating an inflammatory response directly affecting the heart 4 , 8 .…”
mentioning
confidence: 99%
“…One of the key cardiovascular manifestations observed in NiV infection is myocarditis, characterized by myocardial inflammation 4 , 5 . Myocarditis can lead to myocardial dysfunction, arrhythmias, and even heart failure 5 7 . Histopathological studies have revealed lymphocytic infiltrates in the myocardium of NiV-infected individuals, indicating an inflammatory response directly affecting the heart 4 , 8 .…”
mentioning
confidence: 99%